In vitro and in ex vivo effects of vitamin D on regulation of vascular tone - Alharbi, Laila (2016)
Hypertension is a key factor in the progression of cardiovascular diseases, and vitamin D is now recognised as a significant factor affecting blood pressure. Low serum concentrations of calcidiol may be related to the pathogenesis and progression of hypertension. The effect of both calcidiol and calcitriol on the proliferation and gene expression of HUVECs and on the subsequent proteins produced, secreted, or regulated by endothelial cells is investigated. This was followed by studies on the thoracic and abdominal segments of aortas isolated from adult female Wistar rats to determine direct vasomodulatory effects of calcitriol using a wire myograph system. The result showed that calcitriol (10-13 M) significantly enhanced the proliferation of HUVECs whereas a relatively high concentration of calcidiol (10-9, 10-7 M) significantly inhibited cell proliferation after the same incubation period: 24 and 48 hours. Calcidiol had the greatest effect on the expression of genes, particularly those involved in regulating blood pressure, with decreased ET-1 mRNA expression, and there was a significant increase in eNOS mRNA relative to the control, particularly with 10-11 M of calcidiol. However, calcitriol had little effect on the expression of these genes so its effects on blood vessels may relate to non-genomic mechanisms. Ex vivo studies have shown that calcitriol acutely reduced endothelium-independent contraction in rat thoracic and abdominal aortas and does not involve NO. The acute effect of calcitriol reduced or inhibited the dose-dependent (10–9 to 10–5 M) contractions induced by PE, and there was a significant inhibition of the subsequent dose-dependent (10–9 to 10–5 M) relaxation induced by acetylcholine. The acute vasorelaxant effects of calcitriol do not appear to be mediated via the AC-cAMP-PKA signalling pathway but were similar to the effects of the Ca2+ channel blocker, verapamil. In summary, this thesis reports novel information regarding the effect of calcitriol on regulation of vascular tone through enhancement of a potential relaxation of arteries in an endothelium-independent manner, which is mediated by a non-genomic mechanism. Future studies need to confirm these results with in vivo studies. Hence, inducing relaxation in smooth muscle cells ex vivo may facilitate to use calcitriol as an antihypertensive drug.